Technologies follow technologies and occasionally social groups - Michael Hübler; Dorothee Christine Bühler (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2023)
An innovative model describing the convergence of technology use at the micro level is introduced. ICT (information and communication technology) ownership, measured as the number of smartphones within a household, depends upon socioeconomic character- istics, such as income, education, technologies and occupation. ICT ownership and the socioeconomic characteristics are specified in relative terms between household pairs. Indicators for jointly belonging to a social group define a new explanatory variable type. Applying this model to survey and geographic data on rural households in Thailand and Vietnam, Heckman-type regressions show that better education and existing technologies unequivocally enhance convergence of ICT ownership among households, whereas the effect of social groups depends on the specific group. Self-employment or employment outside agriculture enhance convergence, whereas farming or employment in agriculture lead to divergence. The results advice policymakers to support the spread of ICT that provides access to valuable information and creates income-generating opportunities.
Keywords: F63; O33; Q12; Q17; Q54; 330; ICT; Smartphones; Technology diffusion; Rural development; Social networks